Single-textured insole for the less affected leg in freezing of gait: A hypothesis - Etoom, Mohammad; Altaim, Thamer Ahmad; Alawneh, Anoud; Aljuhini, Yazan; Alanazi, Fahad Salam; Gaowgzeh, Riziq Allah Mustafa; Alanazi, Abdullah Owaid; Neamatallah, Ziyad; Alfawaz, Saad; Abdullahi, Auwal (Frontiers in Neurology, 2022)
Freezing of gait (FoG) is one of the most widely distributed and disabling gait phenomena in people with Parkinson's disease (PD). The current therapeutic interventions show suboptimal efficacy in FoG. Lower extremity proprioception impairments, especially in the most affected leg, gait initiation hesitation, and gait asymmetry are FoG factors, and there is a need to accurately consider them in terms of therapeutic approaches. Accordingly, we hypothesize that using a single-textured insole for the less affected leg may improve FoG by providing proprioceptive stimulation that enhances sensory processing and reduces gait hesitation and asymmetry. Proprioceptive sensory stimulation for the less affected limb could be more effective than for the double legs that are currently used in rehabilitation settings due to the sensory processing in the less affected basal ganglia being better.